Internalisasi Dan Implikasi Nilai Etika Pergaulan Dalam Pendidikan Agama Buddha Di Tzu Chi Secondary School Jakarta - Putu Finsen (Educatio, 2026)
This study explores how Buddhist Religious Education fosters the internalization of ethical values in social interactions, specifically at Tzu Chi Secondary School Jakarta. It emphasizes the conveyance of Buddhist values from teachers to students within daily school life. Using a qualitative case study approach, data were gathered through in-depth interviews, observations, and documentation of practices and activities. Analysis involved data reduction, presentation, and systematic conclusion drawing. Findings indicate that ethical value internalization occurs in stages through value transformation, transaction, and transinternalization. Teachers play a crucial role in exemplifying and communicating these values. The process enhances students’ interpersonal communication skills, making them more polite, empathetic, and mindful, while also positively influencing their social behavior by fostering respect, care, and harmonious relationships. The study concludes that the internalization of these ethical values effectively shapes students' character, integrating cognitive understanding with practical application in their lives, demonstrating the potency of value-based education at Tzu Chi Secondary School. Kata kunci: Internalisasi nilai, Etika pergaulan, Komunikasi interpersonal, Perilaku sosial, Pendidikan Agama Buddha.